The Juridical Analysis of Court Decisions Regarding Adopted Children in Their Position as Single Heirs - Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
It is human nature to live peacefully and happily with a complete family. As a complement to a family is the birth of children. When the offspring in the form of the desired child is not obtained naturally, it is done by adopting a child. The legal basis for regulating child adoption prior to the enactment of Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption, is carried out based on customary law, sharia law, and also based on a deed of adoption made before a notary, but after the enactment of Government Regulation Number 54 of 2007 concerning Implementation of Adoption child, the adoption of a child must be carried out through a court decision or stipulation. The need for a notary deed here is meant by the existence of a deed made before a notary, the deviations in a child adoption process will be minimized. The act of adopting a child contains juridical consequences that the adopted child has legal standing against the adopter, also includes the right to be able to inherit the wealth left by his adoptive parents at the time of death.